Inovação estratégica no setor elétrico: relatório técnico da implementação do Instituto de Ciência e Tecnologia - EQT Lab para o processo de transferência tecnológica do grupo Equatorial - BASTOS, José Vicente da Silva (2025)
Technology transfer is essential for economic growth and technological advancement, fostering innovation across various sectors. Innovation Law No. 10,973/2004 established guidelines for intellectual property and technology transfer. Considering that the Research, Development, and Innovation (PDI) Program, regulated by ANEEL and instituted by Law No. 9,991/2000, mandates compulsory investments in research and energy efficiency within the Brazilian electric sector, this study reported on the implementation of the Institute of Science and Technology (ICT) - EQT Lab by Grupo Equatorial, analyzing its impact on innovation and technology transfer in the Brazilian electric sector as a development agent of the ANEEL PDI Program. The study included a contextualization of the creation and operation of EQT Lab, complemented by a literature review on the topic. The adopted methodology combined document analysis of institutional reports from Grupo Equatorial and the institute, along with public data provided by the regulatory agency concerning research projects in the electric sector. The results demonstrated that EQT Lab significantly improved the management processes of R&D projects, particularly highlighting the evaluation of project success through strategic alignment between internal areas and external partners. These improvements reflected the institute's effectiveness as a catalyst for advancing innovation and optimizing technology transfer processes, serving as a model within the electric sector.